In-Silico Docking of Rubia cordifolia Phytocompounds as Potential MMP-2 Inhibitors for Varicose Vein Management - K. Anusree (International Journal of Biochemistry and Biomolecule Research, 2025)
Varicose veins are one of the most common disorders, affecting the vein structure and function of lower limbs, yet there has been no absolute cure found yet. One of the underlying causes for worsening of the condition is the proteolytic activity of MMPs which are a group of enzymes that affect the extracellular matrix (ECM) surrounding the affected veins. Phytocompounds of Rubia cordifolia (Manjishta) were docked against the MMP-2 protein to check presence of protein-ligand interaction that can predict the possibility of using the best suited ligand as an inhibitor against MMP-2 protein. Out of a total of 37 phytochemicals 17 were found to have the most drug-like properties. The ligands were retrieved after in-silico pharmacology studies and docked against the MMP-2 protein. 6 P-L were found to have lowest BI (less than or equal to -0.9) and RMSD value of 0, which corresponds to highly stable bonding between the molecules. This study gives a possibility of using the screened ligands, Munjistine, Rubiadin, 1,5-Dihydroxy-2-Methylanthraquinone, Purpuroxanthins, Alizarin and 1-Hydroxy-2-Methoxy Anthraquinone, to study their effects on reducing the activity of MMP-2, which can reduce the progression of varicose veins into chronic venous disease.
Keywords: MMP-2; Munjistine; Rubia cordifolia; Varicose veins; molecular docking